Contact and Communication in the Formation of Harmonious Circle, Surat Al-Tawheed as a Model: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Falih Abdullah SHalahi, Dr. (lark, 2022)
This study, seeks to elicit the depths of the contact-communication mechanisms and their acted-out movement, then, reveals what they are loaded (namely, contributed) which raised by each concept, and then exposes argumentative problems in their presence, thus, it violates their functions. Throughout this study, there is a movement, indicating its continual (viz., direct) form, from the one to the multiple, which creates the descending form, representing the contact basis. Whilst, from the multiple ones to the one, which makes the ascending form, reflecting communicational root. Strictly speaking, this study is based on the communicative dimension, because it represents the prognostic and the solution from the authority of the exclusionary mind, and the supremacy of the multilateral mind via a mutual shared, which is the fusion of ideas with each other, to establish an optimal human society